The effects of changing the remating interval according to the previous litter size on the reproductive performance of the doe rabbit - López M.; Sierra I.; Vicente F.; Conesa A. (Rabbit production in hot climates, 1994)
The reproductive response of 35 Gigante de España does was studied being subjected to reproductive rhythms conditioned by the prolificity of each parturition. The does acceptance rate was seen to decrease when the remating interval was prolonged (87.19 per cent for the intensive rhythm dropping until 73.08 per cent during the extensive rhythm) whereas the pregnancy and fertility rates grew (52.94, 79.33, 82.46 and 85.33 per cent positive pregnancies during the intensive, semi-intensive, extensive and weaning rhythm, respectively, and the fertility was 52.94, 76.00, 80.70 and 83.33 per cent). Fertility of second mating was high in the intensive rhythm (84.38 per cent). Prolificity was also higher when the real interval between parturitions was increased, obtaining 6.97 total pups per litter for the intensive rhythm, 8.20 for the semi-intensive, 8.65 per cent for the extensive and 8.66 per cent for the weaning rhythm (P less than 0.01). Prolificity of delayed parturitions due to refuse or non pregnancy also tended to increase when the remating interval became greater. The effect of the reproductive rhythm on the litter size at weaning was not significant. The season, inbreeding and age of the does have also been studied and only the age modified significantly the prolificity and the litter size at weaning.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)